Awareness of Tribal Parents for Enrolling Their Children in Primary Education: Chittagong Hill Tracks - Mallick, Biplob; Popy, Fatema Begum; Yesmin, Fatema (Advances in Social Sciences Research Journal, 2022)
Primary education is the constitutional right in Bangladesh and one of the most basic needs on which the nation is built. Nailing this point the paper is aimed to investigate the awareness level of tribal parents to let their children admission in primary schools. The study sets three research questions focusing the awareness of parents and intends to explore the obstacles in path of education. There are 250 tribal parents selected purposively from Khagrachari district of Bangladesh. The sample size consists two areas of tribal parents urban and rural, both areas are entailed literate and illiterate parents of primary school student. The primary data has been collected based on questionnaire survey. The study selects the variables regarding awareness enrollment initiatives while statistical tool (t-test) is used to know awareness level of tribal parents about enrollment of primary education. Finally, the important thing in all scenarios that the researchers have found significant differences in awareness between rural compare to urban as well as literate and illiterate tribal parents about enrollment on primary education of their children. The identified major challenges are the poverty, insufficient infrastructure, unskilled teacher, lack of awareness and proper monitoring for bridging the gap between home and school through mother tongue-based bi or multilingual education in primary school.